Pengaruh Kualitas Layanan Terhadap Minat Beli dan Kepuasan Pelanggan Sebagai Variabel Intervening pada Charles & Keith Mall Ratu Indah Makassar - Syamnarila, Ayu Putri; Efendi, Ahmad; Abdullah, Wahidah - (Study of Scientific and Behavioral Management, 2022)
: This study aims to determine the effect of service quality on purchase intention mediated by customer satisfaction at Charles & Keith Mall Ratu Indah Makassar. This study uses primary data and secondary data, the sampling technique in this study is using a non-probability sampling technique using the Joseph Hair formula, so that the number of samples in this study is 140 respondents. The data analysis technique in this study is using Structural Equation Modeling (SEM) using the help of SmartPLS version 3.0 for windows, which is directed to answer the problem formulation or hypothesis that has been formulated in this study and is used to test the relationship of service quality variables to buying interest directed to answer the formulation of the problem or hypothesis that has been formulated in this study and is used to test the relationship between the buying interest variable and the customer satisfaction variable as a mediating variable. The results of this study indicate that service quality has a positive effect on customer satisfaction, customer satisfaction has a positive effect on buying interest, service quality has a positive effect on buying interest, and service quality has a positive effect on buying interest through customer satisfaction at Charles & Keith Mall Ratu Indah Makassar consumers.